Capsid amino acids at positions 247 and 270 are involved in the virulence of betanodaviruses to European sea bass - Moreno García, Patricia; Souto-Pereira, Sandra; Leiva Rebollo, Rocío; Bandín Matos, Isabel; Alonso-Sánchez, María del Carmen (Springer Nature, 2019)
European sea bass (Dicentrarchus labrax) is severely afected by nervous necrosis disease, caused by nervous necrosis virus (NNV). Two out of the four genotypes of this virus (red-spotted grouper nervous necrosis virus, RGNNV; and striped jack nervous necrosis virus, SJNNV) have been detected in sea bass, although showing diferent levels of virulence to this fsh species. Thus, sea bass is highly susceptible to RGNNV, whereas outbreaks caused by SJNNV have not been reported in this fsh species. The role of the capsid protein (Cp) amino acids 247 and 270 in the virulence of a RGNNV isolate to sea bass has been evaluated by the generation of recombinant RGNNV viruses harbouring SJNNV-type amino acids in the above mentioned positions (Mut247Dl965, Mut270Dl965 and Mut247+270Dl965). Viral in vitro and in vivo replication, virus virulence and fsh immune response triggered by these viruses have been analysed. Mutated viruses replicated on E-11 cells, although showing some diferences compared to the wild type virus, suggesting that the mutations can afect the viral cell recognition and entry. In vivo, fsh mortality caused by mutated viruses was 75% lower, and viral replication in sea bass brain was altered compared to non-mutated virus. Regarding sea bass immune response, mutated viruses triggered a lower induction of IFN I system and infammatory response-related genes. Furthermore, mutations caused changes in viral serological properties (especially the mutation in amino acid 270), inducing higher seroconversion and changing antigen recognition.
Keywords: Lubinas - Virus; Betanodavirus; RGNNV; SJNNV; Recombinant